Next Steps in Business Conversion: Supporting Innovation and Entrepreneurship - Pages, Eric (Maine Policy Review, 1994)
Defense conversion is a major issue confronting Maineand other states that are threatened with the loss of major military and civilian defense facilities. The closing of Loring Air Force Base this year has made real to most Mainecitizens the rapidly changing nature of the state’s defense infrastructure. As the anxiety increases about the future of remaining defense facilities, both the public and private sectors are working to develop meaningful conversion programs and policies. The latter was the focus of a statewide conference on defense conversion, "From Defense to Offense" held last June in Portland. This article by Eric R. Pages is the first of five articles in this issue of Maine Policy Review focused on the defense conversion issue, some of which are based on presentations made at the Maine Science and Technology Foundation-sponsored conference.